CHARACTERISTICS OF CHRONIC GASTRODUODENITIS PREVALENCE AND MORBIDITY INDEXES AND TENDENCY OF THEIR DYNAMICS IN KHARKOV AND DNEPROPETROVSK REGIONS - Gravirovska, N. G.; Zalyubovskа, О. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Study of regional prevalence and morbidity indexes of chronic gastroduodenitis inKharkovandDnepropetrovskregions and their dynamics within 10 years allowed to determine their substantial discrepancy and fluctuation. Increase of growth rate of prevalence (up to 110,8%) and morbidity (up to 220,9%) inKharkovregion, that is 13,6 times higher than average statistical index inUkraine, has been determined. Study of such tendency reasons on the model of polyclinics showed that these indexes are significantly higher in the industrial area of the city with reduced standard of living of the population than in the area with more satisfactory social conditions of the population. The results are a cause to improve the dispensary methods using the advances of modern medicine.